Growing convergence research: Coproducing climate projections to inform proactive decisions for managing simultaneous wildfire risk - Cullen, Alison C.; Prichard, Susan J.; Abatzoglou, John T.; Dolk, Alexandra; Kessenich, Lee; Bloem, Sunniva; Bukovsky, Melissa S.; Humphrey, Reed; McGinnis, Seth; Skinner, Haley; Mearns, Linda O. (Risk analysis, 2023)
We apply a convergence research approach to the urgent need for proactive management of long‐term risk associated with wildfire in the United States. In this work we define convergence research in accordance with the US National Science Foundation—as a means of addressing a specific and compelling societal problem for which solutions require deep integration across disciplines and engagement of stakeholders. Our research team brings expertise in climate science, fire science, landscape ecology, and decision science to address the risk from simultaneous and impactful fires that compete for management resources, and leverages climate projections for decision support. In order to make progress toward convergence our team bridges spatial and temporal scale divides arising from differences in disciplinary and practice‐based norms. We partner with stakeholders representing US governmental, tribal, and local decision contexts to coproduce a robust information base for support of decision making about wildfire preparedness and proactive land/fire management. Our approach ensures that coproduced information will be directly integrated into existing tools for application in operations and policy making. Coproduced visualizations and decision support information provide projections of the change in expected number of fires that compete for resources, the number of fire danger days per year relative to prior norms, and changes in the length and overlap of fire season in multiple US regions. Continuing phases of this work have been initiated both by stakeholder communities and by our research team, a demonstration of impact and value.